Fundamentals of educational research and data analysis a Pafte textbook development project - Padua, Robert N. (Katha Pub., 1998)
Purpose: A book that "attempts to show the strong connection between research and statistics. It deals with model building rather than computations. Useful either as a textbook or a reference material for experts in the field."